Towards a social investment welfare state? Ideas, policies and challenges - Morel, Nathalie 1976-; Palier, Bruno 1966-; Palme, Joakim 1958- (Policy, 2012)
This book maps out the contours of the European 'social investment' strategy, both at the ideational level and in terms of the policies implemented throughout Europe. It will appeal to both social policy scholars and policy experts
Title from publisher's bibliographic system (viewed on 01 Sep 2022)
Keywords: Europäische Union; Sozialpolitik; Mitgliedsstaaten; Wohlfahrtsstaat; European Union countries / Social policy; European Union countries / Social conditions / 21st century; Aufsatzsammlung